MODEL OPTIMALISASI PELAYANAN KONSUMEN PENERANGAN JALAN PLN DI JAWATENGAH - Aman Santoso (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2008)
The service of electricity consumer has no optimal get according toUUNo. 20 / 2002 (Electricity Act). The Local Regulation in City / Regency at Central Java has just regulated general lighting tax taken and managed by Department of Income Affair. The aspect of electricity service has no mentioned from the aragement of duty and right of electricity commodity contract and there is no mechanism of supervision for electricity consumer. For those needs maximization of PLN sheet lighting consumer service model.